Authority Having Jurisdiction - Local Codes and the IBC - Racz, Richard (McGraw-Hill's AccessEngineering., 2023)
This video covers the topic of local jurisdictions and the differences between local codes and the IBC. We discuss examples of real world differences between local codes and the IBC and common decisions a design professional needs to make during the design of a structure.